Simulating Extreme Environmental Conditions via Mental Imagery: The Case of Microgravity and Weight Estimation - Gatti, Matteo; Palumbo, Rocco; Di Domenico, Alberto; Mammarella, Nicola (Frontiers in Psychology, 2022)
Mental imagery can be used for recreating an extreme environment experience. Here we assessed whether microgravity effects over cognition, that typically occur during a space mission, may be reproduced via mental imagery. Participants were randomly assigned to one of two conditions in which they were guided to imagine to be 1) in outer space or 2) in a nature scenario and subsequently estimate the weight of common objects. We found that only for those who engaged in a space scenario imagery, there was a decrease in object weight estimation compared with a prior rating. This finding is the first to indicate that the effects of weightlessness on cognition can be simulated via an imagery-based technique and add to the ongoing debate about the importance of trying to disentangle the effect of microgravity alone on human performance. Moreover, our findings ultimately suggest that imagery can be used as a less expensive simulated scenario for studying the impact of extreme environmental conditions over astronauts’ cognition and behaviour.